1974
DOI: 10.1002/1097-0142(197410)34:8+<1347::aid-cncr2820340803>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to virus-caused cancers

Abstract: Members of four different groups of animal viruses are known to cause cancer in animals. (Only two of them, the leukoviruses and herpesviruses, cause cancer in nonlaboratory situations.) All the members of these groups of viruses form integrated viral DNA in infected cells. However, the efficiencies with which they cause cancer vary by over a dozen orders of magnitude. These differences in efficiency are a result of differences in efficiency of formation and expression of the genes for neoplastic transformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

1974
1974
1978
1978

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…These studies clearly demonstrate that the same region on the ASV genome is utilized for provirus integration in different ASV-transformed cell lines. A central observation in the study of DNA and RNA tumor viruses is the persistence of viral genetic information in the host genome of the transformed cell (1,2). Transformation of mammalian cells by the DNA tumor virus simian virus 40 (SV40) involves the covalent insertion of the viral DNA into the host cell genome (3).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These studies clearly demonstrate that the same region on the ASV genome is utilized for provirus integration in different ASV-transformed cell lines. A central observation in the study of DNA and RNA tumor viruses is the persistence of viral genetic information in the host genome of the transformed cell (1,2). Transformation of mammalian cells by the DNA tumor virus simian virus 40 (SV40) involves the covalent insertion of the viral DNA into the host cell genome (3).…”
mentioning
confidence: 99%
“…These results imply that the site of SV40 DNA integration in the cellular genome is not unique and that the SV40 sequences involved in integration are not confined to a specific region of the viral genome (4,5). Transformation of mammalian cells by RNA tumor viruses requires the formation of a DNA copy (provirus) of the viral RNA and the integration of the provirus into the host genome (2). Molecular hybridization studies have shown that avian sarcoma virus (ASV)-transformed mammalian cells contain one to two copies of covalently integrated provirus per cell and that normal mammalian cells contain little if any DNA sequences homologous to the ASV genome (6)(7)(8).…”
mentioning
confidence: 99%
“…Avian RNA tumor viruses contain several species of RNA, the largest of which is believed to be the genetic material (1). From the sedimentation coefficient (60-70S) and the relative electrophoretic mobility the molecular weight of this RNA was estimated to be about 107 (2)(3)(4).…”
mentioning
confidence: 99%
“…Samples (1-20 ,g total RNA) were annealed with 0.05-0.1 ,ug of poly(dC)-DNA in 50 1 of 0.5 M NaCl-10 mM Tris-HC1 (pH 7.5) containing 1 Mg of oligo(C)&20. After 4 hr at 660, 2 Mg of poly(U) (Miles Laboratories, Elkhart, Ind.) were added and labeled hybrid was determined by poly(I)-Sephadex chromatography.…”
Section: Methodsmentioning
confidence: 93%
“…Progeny RNA would subsequently be produced by transcription of the DNA (1-3). While-the first part of the hypothesis is supported by a number of findings (1)(2)(3), the only evidence for DNA-dependent viral RNA synthesis is provided by the observations that actinomycin D inhibits virus formation (4,5) and that virus mutants are generated by exposure of infected cells to brornodeoxyuridine (6). Although the inhibition experiment demonstrates the requirement for a DNA-dependent step, it does not show that the inhibitor is acting directly on viral RNA synthesis, rather than, for instance, by preventing synthesis of protein(s) required for viral RNA replication.…”
mentioning
confidence: 94%